SERUM LEPTIN AND ADIPOSITY INDICATORS IN INFERTILE FEMALES OF REPRODUCTIVE AGE GROUP - Senghor, Arul; Shivashekar, Meera; Vinodhini, Vm (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: This study was designed to evaluate the interrelationship of adiposity indicators such as body mass index (BMI), waist circumference (WC), hip circumference, waist–hip ratio and waist height ratio, body adiposity index (BAI) in obese and non-obese female individuals unable to conceive. And also to correlate serum leptin levels with adiposity indicators in infertile females of reproductive age group. Materials and Methods: Infertile females of reproductive age group were classified as obese and non-obese individuals based on BMI and waist–hip ratio. Serum leptin levels were estimated and correlated with adiposity indicators using Pearson's correlation statistical analysis. Results: The mean age and duration of infertility were high in obese than the non-obese infertile females. Leptin showed significant positive correlation with WC, waist hip ratio (WHR), and waist/height ratio than the routinely done BMI which had low positive correlation. BAI had mild positive correlation with leptin. Conclusion: WC and WHR are simple convenient non-invasive tools that can differentiate the type of obesity. Adiposity indicators guide the physician to identify the infertile female individuals who require preliminary steps toward weight reduction before starting the right line of therapy to correct their hormonal imbalance.